2021
DOI: 10.3390/ijerph18031074
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Therapeutic Physical Exercise in Patients with Amyotrophic Lateral Sclerosis over Time

Abstract: Background: the main objective of this study was to analyze the potential short-, medium- and long-term effects of a therapeutic physical exercise (TFE) programme on the functionality of amyotrophic lateral sclerosis (ALS) patients, measured with the Revised Amyotrophic Lateral Sclerosis Functional Scale (ALSFRS-R) scale. Methods: a systematic review of the PubMed, SCOPUS, Cochrane, Scientific Electronic Library Online (Scielo), Physiotherapy Evidence Database (PEDro), Cumulative Index of Nursing and Allied He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
0
18
0
9
Order By: Relevance
“…In ALS, a systematic review and meta-analysis including 322 patients showed increased functionality and vital capacity with no effect on muscle strength or quality of life [ 195 ]. A more recent systematic review corroborated the effect of exercise on functional abilities in patients with MS in the short, medium and long terms [ 201 ]. In the context of HD, a preclinical model of HD exercise was able to delay the onset of the disease and cognitive impairment [ 202 ].…”
Section: Exercise and Gut Microbiotamentioning
confidence: 90%
“…In ALS, a systematic review and meta-analysis including 322 patients showed increased functionality and vital capacity with no effect on muscle strength or quality of life [ 195 ]. A more recent systematic review corroborated the effect of exercise on functional abilities in patients with MS in the short, medium and long terms [ 201 ]. In the context of HD, a preclinical model of HD exercise was able to delay the onset of the disease and cognitive impairment [ 202 ].…”
Section: Exercise and Gut Microbiotamentioning
confidence: 90%
“…However, in humans, research data are less clear. Overall, it seems that the best option to prevent the onset of fatigue and see improvements in ALS patients is an exercise of moderate intensity and not very high frequency, combining strength and aerobic endurance [ 121 ].…”
Section: Metabolic Alteration In Neurodegenerative Diseasesmentioning
confidence: 99%
“…For example, in 2018, a randomized controlled trial conducted by Clawson's team demonstrated that exercise programs contained resistance, endurance, and stretching (or range of motion) exercises are safe to be performed with the specified regimen without any worsening of outcomes as related to ALS function and can be tolerated showing high compliance over a long term (Clawson et al, 2018 ). A systematic review published in 2021 identified that therapeutic physical exercise could contribute to slowing down the deterioration of the musculature of patients with ALS and facilitating the performance in daily life activities in the short-, medium, and long term (Ortega-Hombrados et al, 2021 ). In addition, an improved overall functional score, muscle strength, and quality of life in ALS patients had been reported following a period of exercise intervention (Jensen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%